THE EFFECT OF WORK ENVIRONMENT, ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CULTURE ON PERFORMANCE THROUGH EMPLOYEE DISCIPLINE OF BPBD ROKAN HULU REGENCY - Suparno Suparno; Sopiah Sopiah (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The aim of this study was to analyze “organizational culture, work environment and organizational commitment to employee performance” through the employee discipline of BPBD in Rokan Hulu Regency. The data sources of this study were the respondents of BPBD employees in Rokan Hulu Regency. It consisted of 46 samples as respondents. Descriptive analysis was chosen as the data analysis technique, to see the validity of the data, reliability and validity tests were used, then the auter model test and the inner model test in PLS SEM. The results of the study indicated that: Sub Structure 1 showed that work discipline was directly influenced by the work environment, organizational culture and commitment. Sub structure 2 showed that employee performance was directly affected by “work environment, organizational culture, organizational commitment & work discipline. Furthermore, the contribution from sub structure 1, that the contribution of the effect of work environment variables, organizational culture variables & organizational commitment variables was 73.6% on work discipline variables, and contributions from sub structure 2, work environment variables, organizational culture variables, organizational commitment variables & the work discipline variable was 52.8% of the employee performance variable.